Sastra sebagai Kritik Sosial : Ketidakadilan yang Dialami Masyarakat dalam Sajak ‘Orang Kepanansan’ Karya W.S Rendra - Dhini Kusuma Lestari; Dwi Wahyu Candra Dewi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This article examines the role of literature as a medium for social criticism. Literature is not merely a collection of beautiful words; it also functions to convey emotions, ideas, and criticism regarding social issues. Literature can portray societal conditions and various issues veiled in public discourse, fostering debate, reflection, and acting as a catalyst for social change. This article specifically analyzes W.S. Rendra's poem "Orang Kepanasan" (People Overheated) as a clear example of how literature can serve as a medium for social critique.Using a descriptive qualitative approach and documentation method, this study identifies various forms of injustice, including social inequality, legal injustice, and political injustice, as represented in the poem. Rendra employs symbolism and precise language to express public dissatisfaction, even if not explicitly. The per-stanza analysis of the poem reveals sharp criticism that depicts the limited lives of the marginalized confronting luxury and power. Thus, this article affirms that literary works have a cumulative role in shaping public opinion, fostering critical thinking about surrounding circumstances, and disseminating critical ideas, even if change does not occur instantaneously.